ISSUES OF BUILDING AN EFFECTIVE OCCUPATIONAL SAFETY MANAGEMENT SYSTEM IN ELECTRICAL INSTALLATIONS OF A MODERN ENTERPRISE - Harasymchuk, Igor; Potapskyi, Pavlo; Vusatyi, Mykola; Pecheniuk, Andrii (Public Management and Policy, 2025)
The article is devoted to the research and development of solutions to problems hindering the creation of an effective occupational safety management system in the electrical installations of modern enterprises. The work thoroughly examines both the theoretical foundations of management and the unique specifics of hazards in the power industry, as well as the complex issues that arise when implementing an occupational safety management system. The study explores the basic principles and concepts of an occupational safety management system, which are the fundamental basis for any management system. Particular attention is paid to the specifics of safety in electrical installations, where every action is associated with a high risk of electric shock, the influence of electromagnetic fields, static electricity, and the danger of an electric arc. In the central part of the article, the problems of building an occupational safety management system are systematized into three main groups. Organizational problems include the lack of a clear management structure and ineffective communication. Technical problems relate to outdated equipment and the lack of proper protection. At the same time, the human factor and psychological issues, such as ignoring rules due to routine, overconfidence, stress, and fatigue, are recognized as the most challenging obstacles. Based on this analysis, the article proposes comprehensive solutions and mechanisms to address the identified problems. This includes improving the organizational management structure to create a unified chain of command and effective feedback channels. A special emphasis is placed on modernization and innovation as a key tool for risk reduction. This involves implementing real-time monitoring systems, using remote control, and VR simulators that allow for training personnel without risk to life. Furthermore, the paper highlights the importance of enhancing the role of the human factor through the implementation of continuous training and education for all categories of personnel. It proposes creating an effective system of incentives for compliance with safety standards and accountability for their violation, which motivates a conscious attitude towards safety. The materials of the article are a valuable source of information for occupational safety specialists, enterprise managers, engineering and technical personnel, and anyone seeking to improve safety levels in the power industry.